2020
DOI: 10.2174/1574886314666190726154238
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Different Sedatives for Colonoscopy

Abstract: Background & Aims: Sedation and analgesia are important elements of endoscopic examinations; sedation for colonoscopy aims to relieve patient discomfort and anxiety, improve the outcome of the examination, diminish the patient’s memory of the event and achieve comfortable and technically successful endoscopic procedure. Methods: Our prospective study was carried out on 150 patients who were referred for colonoscopy; they were divided into two groups based on the pre-endoscopic sedation given for them: pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
0
6
1
Order By: Relevance
“…Among them,4.2% patients had nausea with or without vomiting and 2.9% patients had vomiting with or without nausea. The incidence of nausea or vomiting in our study is relatively lower than other similarly endoscopic studies [4,5]. It is obviously that the incidence of nausea is higher than the incidence of vomiting after this painless inspection.…”
Section: Discussioncontrasting
confidence: 66%
“…Among them,4.2% patients had nausea with or without vomiting and 2.9% patients had vomiting with or without nausea. The incidence of nausea or vomiting in our study is relatively lower than other similarly endoscopic studies [4,5]. It is obviously that the incidence of nausea is higher than the incidence of vomiting after this painless inspection.…”
Section: Discussioncontrasting
confidence: 66%
“…However, drug interactions may change the pharmacological effects of individual drugs and increase the occurrence of adverse reactions. 22 Remimazolam, a recently developed ultrashort-acting benzodiazepine, shows a high affinity to GABA receptors and increases the frequency of chloride channel opening in the cerebral cortex, limbic system, midbrain, brainstem, and spinal cord. 23,24 The pharmacokinetics and pharmacodynamics of RT are similar to those of remimazolam.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, the risk of PONV was equal in each group, as expressed by the Apfel score ( Table 3 ), and despite the group allocation, only 3 patients out of 158 included in the final analysis suffered from PONV: two from the control group (3.8%), one from the AoA group (1.9%), and none from the SE group, which did not prove statistically significant ( p = 0.25). Seleem et al [ 38 ], in a study concerning different intravenous anesthesia modalities in patients undergoing CP, found that 28 out of 75 patients receiving propofol with FNT complained of PONV, as compared to 8 out of 75 patients receiving propofol with ketamine, which was statistically significant ( p = 0.0001). In comparison to the current study findings, they achieved poorer outcomes, probably due to the fact that they titrated FNT according to the observance of hemodynamic parameters, which may not necessarily properly reflect the demand for OA [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Seleem et al [ 38 ], in a study concerning different intravenous anesthesia modalities in patients undergoing CP, found that 28 out of 75 patients receiving propofol with FNT complained of PONV, as compared to 8 out of 75 patients receiving propofol with ketamine, which was statistically significant ( p = 0.0001). In comparison to the current study findings, they achieved poorer outcomes, probably due to the fact that they titrated FNT according to the observance of hemodynamic parameters, which may not necessarily properly reflect the demand for OA [ 38 ]. Bergmann et al [ 39 ] found no difference between the groups with regard to the rate of IawR using the anesthetic remifentanil/propofol-based modalities with SE only versus AoA guidance in outpatient arthroscopic orthopedic anesthesia.…”
Section: Discussionmentioning
confidence: 99%